Derivation and application of the stream of variation model to the manufacture of ceramic floor tiles. Issue Volume 30:Issues 4(2018) (2nd October 2018) - Abellán-Nebot, José V.
ABSTRACT: One of the main problems in the manufacture of floor tiles is the dimensional variability of the ceramic product, which leads to the product having to be classified into different dimensional qualities with an increase in cost. In this article we propose a novel way of modelling the dimensional variability of ceramic floor tiles by the adaptation of the Stream of Variation model. The proposed methodology and its potential applicability contribute to the integration of process knowledge in the ceramic tile industry and allow tile manufacturers have a new methodology for process improvement, variation reduction and dimensional control.